The Direct Anterior Approach versus the Posterolateral Approach on the Outcome of Total Hip Arthroplasty: A Retrospective Clinical Study. Issue 10 (3rd September 2022) - Wang, Zhao; Bao, Hong‐Wei; Hou, Jing‐Zhao; Ju, Bin; Wu, Can‐Hua; Zhou, Yao‐Jiang; Gu, Xiao‐Ming; Wang, Hai‐Hong
Abstract : Objective: To compare the clinical results of the direct anterior approach (DAA) and posterolateral approach (PLA) in total hip arthroplasty (THA) patients. Methods: From January 2017 to September 2019, 80 patients who received primary THA in our hospital were retrospectively selected based on the propensity score matching (PSM) method. Baseline characteristics of patients who underwent the DAA and PLA were collected. Moreover, the incision length, intraoperative blood loss, operative time, length of stay, and Harris hip score were compared between patients in the two groups. The CK level was used to assess muscle damage between patients in the DAA and PLA groups. The complications of these two approaches were also evaluated at patients' 12‐month follow‐up evaluation. Results: There was no significant difference in baseline characteristics between patients in the two groups ( p  > 0.05). The patients in the DAA group had a shorter incision length (9.2 ± 0.2 vs 14.7 ± 0.5, respectively; p  < 0.05) and shorter length of hospital stay (9.5 ± 0.7 vs 12.9 ± 0.8, respectively, p  < 0.05) than patients in the PLA group. Moreover, the DAA was associated with a decrease in intraoperative blood loss compared with the PLA (109.1 ± 12.6 vs 305.1 ± 14.1 ml, respectively, p  < 0.05). However, the operation time was longer in patients in the DAA group (130.7 ± 1.7) than in patients in the PLA group (112.6 ± 1.3 min, p  < 0.05). The CK level of patients in the DAA group was lower than that of patients in the PLA group ( p  < 0.05). The CK level at 48 h post‐surgery was negatively correlated with the Harris hip scores at 6 months after THA ( r  = −0.538, p  = 0.000). Compared with patients in the PLA group, the muscle strength of patients in the DAA group was significantly higher than that of patients in the DAA group at 4 days ( p  < 0.05) and 7 days ( p  < 0.05) after THA. The Harris hip scores of patients in the DAA group and PLA group were 81.0 ± 0.8 vs 70.8 ± 0.7 at 6 weeks, 93.4 ± 0.9 vs 86.4 ± 0.6 at 3 months, and 96.8 ± 1.1 vs 93.4 ± 0.8 at 6 months, respectively, both p  < 0.05. There was no significant difference in the incidence of complications between patients in the DAA and PLA groups ( p  > 0.05). Conclusion: DAA was superior to the PLA in improving hip function after THA. Compared with the PLA, the DAA could reduce muscle damage, which is negatively correlated with hip function. Further multi‐institution studies are required with longer follow‐up durations, and larger patient populations are needed to provide more definitive conclusions. Abstract : Comparison of postoperative gross appearance and X‐ray images between patients who underwent the direct anterior approach (DAA) and posterolateral approach (PLA) for total hip arthroplasty (THA).